Supply Chain Structure and Performance of the Salted Fish Industry: Evidence from Baai Island, Bengkulu - Suli Harni; Eko Sumartono; Herri Fariadi (PT. Sangadji Media Publishing, 2026)
Purpose - The salted fish supply chain on Baai Island, Bengkulu City, continues to rely on traditional management practices characterized by limited operational efficiency, low information transparency, and inadequate quality standardization, which constrain overall supply chain performance. This study aims to analyze the product, information, and financial flows within the salted fish supply chain and evaluate its overall performance. Design/methodology/approach - This study combined observations, interviews, and questionnaires involving 49 purposively selected fishermen, processors, and traders to analyze product, information, and financial flows and to evaluate marketing margins and supply chain performance. Findings - The results indicate that the product flow follows a sequential channel from fishermen to processors, traders, and ultimately consumers. Information flow remains limited, particularly regarding market prices and the availability of raw materials, while financial transactions primarily occur through direct cash payments between supply chain actors. Marketing margins varied across product types, ranging from IDR 5,000/kg to IDR 14,000/kg, with an average margin of IDR 8,333.33/kg. The overall supply chain performance achieved a performance index of 79.18%, indicating a good level of performance. Practical implications—The findings provide practical insights for processors, traders, and local government agencies to improve supply chain efficiency through enhanced information sharing, stronger coordination among supply chain actors, and more transparent financial and marketing practices. Novelty/Originality - This study develops an integrated assessment framework that simultaneously evaluates product flow, information flow, financial flow, marketing margins, and supply chain performance within a small-scale salted fish supply chain.